Study of groundwater properties and behaviour using geospatial techniques - Agarwal, Vivek (2022)
Groundwater contributes a significant proportion of the earth’s freshwater and is essential to sustain life on earth, but its availability in spatial and temporal dimensions is not uniform. With the advent of efficient pumps and rural electrification, global groundwater extraction increased from 312 km3/year in the 1960s to 800 km3/year in 2000s; approximately 70% of this extraction is used for agriculture. About half of domestic human water consumption in urban areas is from groundwater. The ever-increasing dependence on groundwater has led to its depletion across various parts of the world. This trend must be reversed to sustain the critical role of groundwater. Groundwater monitoring based on validated data can provide information that can guide decision making to decrease groundwater stress on local and global scales. This thesis aims to monitor spatio-temporal changes in groundwater and related phenomena (like land subsidence) using geospatial techniques like InSAR, GRACE, GIS, data analysis and data visualisation. The over-extraction or rebound of groundwater can lead to land deformation because of the change in effective stress of underground sediments. Groundwater-induced land movement can cause damage to property and resources, and hence it must be monitored for the safety and economics of a city. This thesis explores the suitability of Persistent Scatterer Interferometric Synthetic Aperture Radar (PSInSAR) to measure land deformation and different senor-software for InSAR processing. The groundwater quantity variation and resulting land deformation for London using InSAR and Gravity Recovery and Climate Experiment (GRACE) between 2002-2010 were analysed. Long-term, decreasing, complex, non-linear patterns in the spatial and temporal domains from both InSAR and GRACE datasets were observed. The land movement velocities varied from -6 to +6 mm/year, and their reliability was validated with observed GNSS data by conducting a two-sample t-test. The average groundwater loss estimated from GRACE was found to be 9.003 MCM/year. The results demonstrate that InSAR and GRACE complement each other and can be an excellent source of monitoring groundwater for hydrologists. Then groundwater induced subsidence for London and the National Capital Territory of Delhi (NCT-Delhi) between 2016 and 2020 were studied. The land movement velocities were found to vary between -24 mm/year to +24 mm/year for London and between -18 mm/year to +30 mm/year for NCT-Delhi. This land movement was compared with observed groundwater levels and spatio-temporal variation of groundwater. A 1-D mathematical model was used to quantify land deformation for a given change in groundwater level. It was broadly observed that when large volumes of groundwater are extracted, it leads to land subsidence, and when groundwater is recharged, surface uplift is witnessed. However the local geology, did play an important role in the extent of subsidence, which was considered in the mathematical model. The increased pressure on groundwater can cause spatio-temporal changes in its quality because of various atmospheric stimulations, varied geology, variation in subsurface mineralogy and factors controlling residence times. Moreover, the variation of groundwater quality is vital for the sustainable management and safety of groundwater. Thus, the variation in groundwater quality is analysed from observed data for London between 2000 and 2020. The data samples were used from 500 wells in the London basin, and the data is provided in the free open access domain by Environment Agency. The overall groundwater in London was found to be dominant magnesium bicarbonate type which typically represents shallow fresh groundwater, and spatio-temporal variations of hardness, sodium, and dissolved oxygen (DO) were also studied. Significant variations in the range of each constituent were found, which was attributed to variation in the geology of the London Palaeogene aquifers and anthropogenic activities. All the case studies help better understand the phenomenon of spatio-temporal variation in groundwater behaviour and associated land deformation for urban cities. The research presented in this thesis can be used to determine whether groundwater is available and suitable for its intended purpose, discover pollutants, examine any spatio-temporal variations, and monitor land subsidence.